Rule-based Interactive Learning Application Model on How to Play Music Instruments - Fanani, Ahmad Zainul; Hastuti, Khafiizh; Syarif, Arry Maulana; Mulyana, Aton Rustandi (International Journal of Emerging Technologies in Learning (iJET), 2020)
This research aims to develop an interactive application to support people learning to play music instruments of orchestra music. Gamelan, a traditional music orchestra from Java, Indonesia was used as the object study. A model of gamelan orchestra learning application was proposed to support an easy way to learn how to play gamelan music instruments. Rule-based method was used to develop an interactive system to learn gamelan music instru-ments. The system was implemented into an application which supports us-ers in independently learning to play orchestra music instruments, especially in remembering notes sequences and playing the note according to the tem-po. An experiment involving two groups consisted of control and treatment groups were conducted to evaluate the proposed learning model. The results shows that the averages skill value of the members of the treatment group were higher than the members of the control group.